Effect of non-degradable protein level in rumen on the in situ ruminal degradation of Bermuda grass (Cynodon dactylon (L.) Pers) cv. Coastcross in buffaloes - Delgado, Denia C.; Franzol?n Neto, R.; Abdalla Gomide, Abdalla (Cuban Journal of Agricultural Science, 2011)
Four buffaloes (Bubalus bubalis) of the Mediterranean breed, with 300 ?12 kg of average liveweight, fitted with rumen cannula, were used in a change-over design to determine the effect of two levels of non-degradable protein in rumen (NDPR) on the in situ ruminal degradability of dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) of Coastcross Bermuda grass (Cynodon dactylon (L.) Pers) hay. The treatments consisted of diets of Coastcross Bermuda grass hay (70 %) and concentrate (30 %) of maize (8.6 %), and whole-plant crude (CS treatment) or extruded soybean (ES treatment) (26.4 %), contributing to 28 and 44 % of NDPR/CP, respectively. The incubation times were 0, 6, 12, 24, 48, 72, and 96 h for the hay, and up to 48 h, for the concentrates. No differences were found between the treatments for the indicators under study. The potential degradability (A+B) of the DM in the hay was of 51 and 48 % for the CS and ES treatments, respectively. The effective degradation (ED), for the passage rates of 0.02 and 0.05 h-1, was lower than 40 % for the DM and NDF, and higher than 45 % for the CP. The results suggested that, under these experimental conditions, the NDPR level in the buffalo diet does not affect the kinetics of the ruminal degradability of Coastcross Bermuda grass hay. Key words: degradability, Coastcross Bermuda hay, Bubalus bubalis, soybean.